2023
DOI: 10.1002/advs.202205668
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy‐Induced Senescence Reprogramming Promotes Nasopharyngeal Carcinoma Metastasis by circRNA‐Mediated PKR Activation

Abstract: Senescence is associated with tumor metastasis and chemotherapy resistance, yet the mechanisms remain elusive. Here, it is identified that nasopharyngeal carcinoma (NPC) patients who developed distant metastasis are characterized by senescence phenotypes, in which circWDR37 is a key regulator. CircWDR37 deficiency limits cisplatin or gemcitabine‐induced senescent NPC cells from proliferation, migration, and invasion. Mechanistically, circWDR37 binds to and dimerizes double‐stranded RNA‐activated protein kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…CircWDR37, instead, exerts its role activating the PKR cascade, which results in the promotion of NF-κB activation, proliferation, and senescence-driven metastasis. In fact, experimentally lowered circWDR37 is correlated with chemotherapy response and favorable survival in nasopharyngeal carcinoma patients treated with gemcitabine or cisplatin [ 38 ]. Indeed, it could represent a possible therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…CircWDR37, instead, exerts its role activating the PKR cascade, which results in the promotion of NF-κB activation, proliferation, and senescence-driven metastasis. In fact, experimentally lowered circWDR37 is correlated with chemotherapy response and favorable survival in nasopharyngeal carcinoma patients treated with gemcitabine or cisplatin [ 38 ]. Indeed, it could represent a possible therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that circRNAs can participate in the progression of cancer by regulating the NF-κB pathway. 27,28 For example, circWDR37 deficiency inhibits chemotherapy-induced proliferation and metastasis of senescent NPC cells in vitro by inhibiting the NF-κB pathway. 27 We found that circRNA_CDKN1A acts by affecting the NF-κB pathway.…”
Section: Knockdown Of Circrna_cdkn1a Activates the Nf-κb Pathwaymentioning
confidence: 99%
“…27,28 For example, circWDR37 deficiency inhibits chemotherapy-induced proliferation and metastasis of senescent NPC cells in vitro by inhibiting the NF-κB pathway. 27 We found that circRNA_CDKN1A acts by affecting the NF-κB pathway. However, this study only preliminarily confirmed the correlation between circRNA_CDKN1A and the NF-κB pathway, as no target gene directly regulated by circRNA_CDKN1A was found.…”
Section: Knockdown Of Circrna_cdkn1a Activates the Nf-κb Pathwaymentioning
confidence: 99%
“…NF-κB is an important transcription factor that promotes inflammatory responses and immune responses, and is also involved in the regulation of apoptosis and senescence. 107, 136 Guo et al 121 demonstrated that circARHGEF28 could negatively regulate the NF-κB pathway by sponging miR-671-5p. Another study proved that circRNF10 inhibited the activation of NF-κB signaling pathway by interacting with DEAH (Asp-Glu-Ala-His) box helicase 15 (DHX15).…”
Section: Nf-κb Signaling Pathwaymentioning
confidence: 99%
“…NF‐κB is an important transcription factor that promotes inflammatory responses and immune responses, and is also involved in the regulation of apoptosis and senescence 107,136 …”
Section: Circular Rnas Regulate Cellular Senescence Via Various Pathwaysmentioning
confidence: 99%